Hubungan Keteraturan Pemeriksaan Antenatal Care dengan Kesiapan Menghadapi Persalinan Pada Ibu Hamil Primigravida Trimester III Pada Masa Pandemi COVID-19 - Putu Meidiana Karmilasari; Asep Arifin Senjaya; I Gusti Agung Ayu Novya Dewi (Poltekkes Kemenkes Denpasar, 2022)
Tendance of the mother and fetus’s health during pregnancy need to be noteworthy. Through regular ANC visits, various information and education related to pregnancy and preparation for delivery can be given to mothers as early as possible. The objective of this research was to determine the relationship between the regularity of antenatal care examinations with readiness to face labor in third trimester primigravida pregnant women during the COVID-19 pandemic. This type of research is an analytic study with a cross-sectional design wich conducted from April to May 2022 used accidental sampling. Data of regularity collected by looking at the history of examinations in the KIA’s book and data of readiness collected by questionnaire. Data analysis univariate used frequency distribution and data analysis bivariate used Spearman Rank correlation test based on significant level p 0.05. The results of the study from 29 respondents showed that there are 55,2 % repondents regulary doing ANC examination and 51,7 % respondents ready for facing delivery. The results of biariate analysis there was an association between the regularity of antenatal care examinations and readiness for childbirth in third trimester primigravida pregnant women during the COVID-19 pandemic with p value: 0.004( 0,05) and r value: 0.517.